2000
DOI: 10.1177/01939450022044755
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Vagal Tone Responses in Preterm Infants

Abstract: The purpose of this study was to examine factors related to vagal tone (VNA) among preterm infants receiving a 10-minute gentle human touch (GHT) intervention three times daily for 10 days. VNA was measured continuously for 10 minutes before, during, and after each 10-minute GHT intervention. Findings indicated that there was a significant relationship between VNA and gestational age, although there were no relationships between VNA and measures of motor activity or behavioral distress. There was no difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
6
6
0
Order By: Relevance
“…Therefore, this study examined the relationship between vagal tone and the other variables of premature infants. Because previous research (Porges, 1983; Harrison et al . 2000) has indicated that characteristics of infants at birth correlate positively with resting vagal tone, the Pearson correlation coefficient was calculated for characteristics of infants at birth and vagal tone during pre‐bathing on the first day of this study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, this study examined the relationship between vagal tone and the other variables of premature infants. Because previous research (Porges, 1983; Harrison et al . 2000) has indicated that characteristics of infants at birth correlate positively with resting vagal tone, the Pearson correlation coefficient was calculated for characteristics of infants at birth and vagal tone during pre‐bathing on the first day of this study.…”
Section: Resultssupporting
confidence: 93%
“…(1991) found that heart period and vagal tone increased during sensory testing and decreased during cognitive testing, with 24 normal infants and 11 regulatory disorder infants (who exhibit fidgeting, irritability, poor self‐calming, intolerance to change, and a hyper‐alert state of arousal) aged from 8 to 11 months. Harrison et al . (2000) reported that there was no difference in vagal tone during baseline, touch and post‐touch for 32 premature infants who received a 10‐min gentle human touch.…”
Section: Discussionsupporting
confidence: 78%
“…In a study using moderate pressure massage, vagal activity increased (Lee, 2007), while, in another study using light pressure stimulation, no changes were noted in vagal activity or weight gain (Harrison, Williams, Leeper, Stem & Wang, 2000). These findings highlight the critical importance of moderate pressure for attaining these effects.…”
Section: Vagal Activity and Gastric Motilitymentioning
confidence: 99%
“…The PNS and SNS are neural systems that originate in the brainstem and contribute to the regulation of organs and systems such as the heart, lungs, salivary glands, adrenal glands, eyes and lacrimal glands, sweat glands, blood vessels, digestive system, and renal system. 9,17 The low-frequency band (Ͻ0.2 Hz) is primarily influenced by the SNS, and to a lesser extent by the PNS, and indicates the response to external challenges. The SNS promotes increased metabolic output to help the body deal with external challenges.…”
Section: Box 2 Physiologic Indicators Of Relaxation Response: Heart mentioning
confidence: 99%